Impact of cash reserve ratio on banks profitability: A study on conventional commercial banks in Bangladesh - Mia, Md Faykuzzaman; Nodi, Masuma Aktar; Mia, Arif; Alam, Shah (Journal of Asian Business Strategy, 2023)
This paper analyzes how banks profitability responds to fluctuations in cash reserve ratio in Bangladesh. Basically, it’s purpose is to examine the effects of Bangladesh Bank practices of employing cash reserve ratio on banking intermediation activities and as a result its profitability, particularly in conventional commercial banking sector. Coefficient of Correlation is used to find out the relation between cash reserve ratio and banks profitability while t-test is utilized for testing hypothesis. Quantitative time series data for 5 years’ time period of 2017-2021 was collected for the study. The researcher selects ten leading conventional commercial Bank as sample. This study highlights the consequences of movement in CRR on banks profitability by using secondary data. The finding of the study is that CRR has negative relation with banks profitability where Return on Assets (ROA) and Return on Equity (ROE) is studied as profitability indicator. It can be concluded that movement in CRR keep inverse impact on conventional commercial banks profitability in the long run by influencing the banks intermediary work. This paper helps the banks to stand strongly and strategically at the time of tight monetary policy when CRR rate increases by informing the inverse impact of this monetary tool.